Our Language, Their Language. Once Again about the Text Variants of Czesław Miłosz’s “Campo dei Fiori” - Wołk , Marcin (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2024)
English version. Original issue: “Archiwum Emigracji” 2011, no. 1–2 (14–15) https://apcz.umk.pl/AE/article/view/AE.2011.002